Transparansi dan Efisiensi Laporan Keuangan Perusahaan Ritel dalam Perspektif Akuntabilitas Keuangan Syariah(Studi pada PT Indomarco Prismatama Bengkulu) - Surya Mauladna; Yosy Arisandy; Rizky Hariyadi (Universitas Muhammadiyah Surabaya, 2025)
This study aims to analyze the extent to which the financial reporting practices implemented by PT Indomarco Prismatama Bengkulu align with the principles of transparency and efficiency from the perspective of Sharia financial accountability. This research employs a descriptive qualitative method using interviews, observation, and documentation techniques. The findings indicate that the company applies a financial reporting system based on general (Pernyataan Standar Akuntansi Keuangan) PSAK standards supported by an Enterprise Resource Planning (ERP) system, which enhances efficiency, although information disclosure remains limited. Efficiency efforts are evident in operational cost control, asset maintenance, and routine internal and external audits. Although PT Indomarco Prismatama Bengkulu is a conventional company and does not explicitly adopt Sharia reporting standards, several accountability principles applied by the company reflect alignment with Islamic financial accountability values